2012
DOI: 10.1002/pssa.201228555
|View full text |Cite
|
Sign up to set email alerts
|

Structural and optical properties of phase‐change amorphous and crystalline Ge1 − xTex (0 < x < 1) thin films

Abstract: Ge1 − xTex thin films were grown using thermal coevaporation deposition. The dielectric functions and the phonon modes of amorphous (a‐) and crystalline (c‐) Ge1 − xTex films were measured using spectroscopic ellipsometry and Raman spectroscopy in order to investigate electronic and vibrational properties of these alloys. Using the second derivative spectra of the dielectric functions of a‐Ge1 − xTex alloys and the standard critical point (SCP) model, we obtained optical transition energies for the a‐Ge1 − xTe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Screening from this charge softens phonons [44] and will also contribute to Raman linewidth broadening. Finally, Park et al [50] have shown that local Te rich phases can exhibit a variety of modes with energies ranging between 120 and 170 cm −1 , the range of the background signal in our high temperature Raman spectra. These modes originate in Te-Te bonds (induced by Ge vacancies) and GeTe 4 edge sharing octahedra.…”
mentioning
confidence: 60%
“…Screening from this charge softens phonons [44] and will also contribute to Raman linewidth broadening. Finally, Park et al [50] have shown that local Te rich phases can exhibit a variety of modes with energies ranging between 120 and 170 cm −1 , the range of the background signal in our high temperature Raman spectra. These modes originate in Te-Te bonds (induced by Ge vacancies) and GeTe 4 edge sharing octahedra.…”
mentioning
confidence: 60%
“…Bulk dielectric functions (1 solid line, 2 dashed line) of some binary compounds of p-block elements, taken from the literature: IV-VI chalcogenide compounds (GeS [56], GeSe [56], GeTe [57], SnSe [58], SnTe [56,59], PbS [43,60], PbSe [56], PbTe [56]); V-VI chalcogenide compounds (Sb2Se3 [56], Sb2Te3 [56], Bi2Se3 [61], Bi2Te3 [62]).…”
Section: Discussionmentioning
confidence: 99%
“…In order to develop devices with better characteristics, understanding material properties are of vital importance. Therefore, optical properties such as dielectric functions, optical band gap, and phonon modes have been studied using ellipsometry and raman spectroscopy [13]. Moreover, the electronic properties of amorphous as well as crystalline phase have been studied for various Ge 1−x Te x compounds [14].…”
Section: Introductionmentioning
confidence: 99%